Produtividade total do trabalho e estrutura produtiva: uma análise da economia brasileira a partir de subsistemas - Santini, Theo; de Acypreste, Rafael (Brazilian Keynesian Review, 2022)
The technical progress of a given economy affects both its economic growth and structural change path. A multi-sector analysis concerning the sectoral evolution of productivity change demands measures that also consider the production chain, thus allowing to capture the propagation effect of technical progress among sectors, which is a fact often ignored by conventional measures. Hence, this investigation intends to evaluate the sectoral total labor productivity behavior in Brazil, between 2000 and 2018, departing from the concept of subsystems. Such methodology allows to be depicted the direct and indirect labour demanded by a given sector, from the other sectors and from itself, to meet final demand requirements. In this vein, it is noted that the industrial sectors have more robust productive chains, but that they have been showing low rates of productivity growth and loss in the labour share in the country. The agricultural sector, on the other hand, showed high productivity growth rates, which indicates high competitiveness, but with a significant reduction in labor requirements. Although this sector has fewer productive chains, it supported to propagate technical progress to other sectors that directly or indirectly acquire their products as inputs.